Kedudukan dan Kewenangan Dewan Komisaris dalam Two-Tier Board System: Evaluasi Efektivitas Pengawasan Berdasarkan UUPT - Bagus Firman Wibowo; Revi fauzi Putra Mina (Universitas Medan Area, 2026)
This study examines the position and authority of the Board of Commissioners within the framework of the two-tier board system as stipulated in Law Number 40 of 2007 concerning Limited Liability Companies (UUPT) and its amendments through Law Number 6 of 2023 concerning the Stipulation of the Perppu on Job Creation. The main issues examined include the extent to which the normative construction of the UUPT is able to effectively operationalize the supervisory function of the Board of Commissioners, as well as the structural obstacles that weaken this effectiveness in Indonesian corporate practice. The study uses a normative juridical method with a statutory, conceptual, and comparative approach. The analysis was conducted on the norms of the UUPT, regulations of the Financial Services Authority (OJK), the principles of corporate law, and governance practices in several jurisdictions that adopt dual and single board systems. The results of the study reveal three main findings: first, the normative design of the UUPT places the Board of Commissioners in a passive, reactive supervisory position, rather than an active, proactive supervisor, thus creating structural gaps in management oversight; second, provisions regarding the independence of independent commissioners are not equipped with an effective enforcement mechanism, making them vulnerable to dominance by majority shareholders; and third, the boundaries of authority between supervision (Board of Commissioners) and management (Board of Directors) often become blurred in practice, giving rise to intraorganic jurisdictional conflicts that weaken the company's accountability and strengthen the inquisitorial authority of the Board of Commissioners, codify measurable independence standards, and clarify the boundaries of authority between company organs.